Edukasi Gizi Seimbang dan Penyakit Degeneratif bagi Lansia Desa Kenongrejo Kabupaten Madiun - Lukas Susanto; Andri Wahyu Utomo; Puri Ratna Kartini; Roy Putra; Desi Kusumawati; Mohammad Arfi Setiawan; Cicilia Novi Primiani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service aims to increase the knowledge of the elderly in Kenongrejo Village regarding balanced nutrition and degenerative diseases. The method of implementing this service was socialization and mentoring. The evaluation instrument for this activity was the help of an evaluation rubric which was then analyzed descriptively. The results of this service showed that the knowledge of the elderly regarding food menu arrangements for the elderly increased by 45%; participants' understanding of various degenerative diseases that occurred in the elderly increased by 30%; awareness of the importance of routine health control for the elderly increased by 42%; participants' motivation in participating in outreach/counseling increased 30%; and implementation of socialization/counseling programs increased 100%. Based on the service activities that had been carried out, socialization and mentoring activities were going well and could provide changes in behavior patterns for the elderly in Kenongrejo Village.